Efektivitas Penggunaan Aplikasi Lingodeer Sebagai Media Pembelajaran Bahasa Jepang Tingkat Dasar - Raihan Yuanda; Muhammad Anggi Lubis; Kharisma Nur Devyanti; Cahya Rudansah; Humannisa Rubina Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the effectiveness of the LingoDeer application as a learning medium for basic level Japanese language learners. A quantitative approach was employed using a One Group Pretest Posttest design involving 50 students from the Vocational School of IPB University. The research instrument consisted of pretest and posttest assessments focusing on three key areas: vocabulary, grammar, and reading skills. Based on the results of the paired sample t-test, a significant improvement was found in all aspects after the use of the application, with the average score increasing from 60.97% to 81.25%. The greatest improvement was observed in vocabulary, followed by reading and grammar. These findings suggest that LingoDeer, with its structured learning system, spaced repetition feature, and interactive exercises, can effectively support the development of Japanese language skills at the beginner level. This study is expected to serve as a reference for educators in selecting appropriate technology-based learning tools to enhance language acquisition.